Ulasan Online Pengunjung Mancanegara dalam Tripadvisor sebagai Bahan Evaluasi terhadap Eksistensi dan Pengelolaan Museum Bali - Anom Hery Suasapha (Universitas Udayana, 2023)
This article discussed the online reviews posted by visitors of Museum Bali on Tripadvisor. The aim is to understand the existence of Museum Bali as a tourist attraction that preserves Balinese cultural artifacts. Inductive category formation-qualitative content analysis was done to analyze the online reviews. The result shows that Museum Bali is an attractive tourist attraction for international tourists from countries with Western cultures. While stating that Museum Bali is a recommended museum with a good display, among other positive comments, the tourists negatively commented that the display materials lacked explanation. Besides, they did not recommend using a tour guide while visiting Museum Bali. Based on the result, this article recommends the management of Museum Bali hold on to its strengths and improve those that are perceived negatively by the reviewer. Improving the quality of interpretation for each displayed collection is crucial while managing the tour guide should also be prioritized.